The Tax Burden on Cross-Border Investment: Company Strategies and Country Responses - Harry Grubert (Center for Economic Studies and ifo Institute (CESifo), 2003)
We look at the tax burden on direct investment from three perspectives. The first section illustrates how the recognition of company tax planning and of the importance of intellectual property affects measures of effective tax rates. It also discusses the methodological issues that arise, such as to which subsidiary the benefits of a multicountry strategy should be attributed. The simulations emphasize the importance of the share of royalties in crossborder income, and of tax planning strategies such as the shifting of debt to high-tax locations. At the same time, evidence on actual company behavior is necessary to limit the range of possible tax avoidance strategies. Otherwise, the effective tax burden on cross-border investment would virtually disappear. Even then, the range of possible estimates is large. The simulations also show how home governments can respond to some types of tax planning by, for example, requiring that parent interest expense be allocated to foreign income. The second section supplements the hypothetical calculations by evaluating the determinants of the actual effective tax rate on overall U.S. manufacturing investment abroad. Among the various components are the location of assets, the location of debt, other forms of income shifting, the share of royalties, and home government repatriation taxes. The results are generally consistent with the simulations in the first section. Somewhat surprisingly, real assets seem more mobile than tax bases, confirming the constraints on tax avoidance. The first two sections demonstrate that it is not the more obvious' features of a tax system, such as whether foreign dividends are taxed or exempt, that are important, but provisions that govern the taxation of royalties, the use of tax haven finance subsidiaries, and the allocation of parent interest expenses to foreign income. The third section introduces host government behavior to see how they tax different types of companies.
Keywords: 330